NOVEL COMPOSITE OF PLASTER KILN DUST-Fe3O4 MAGNETIC NANOPARTICLES AS SORBENT TO UPTAKE CADMIUM (II) IONS FROM CONTAMINATED WATER - Alhussainy, H. Y.; Zwayen, D. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to use composite magnetic plaster kiln dust (MPKD) as a novel low-cost adsorbent reused of by-product plaster kiln dust (PKD) that was considered a source of air pollution. The removal efficiency of cadmium (II) ions was studied as a function of pH (4-7), MPKD mass (0.5- 8 g/L), initial ion concentration (50- 350 mg/L), and shaking time (5- 180 min). The adsorption kinetics of the MPKD was detected as chemical sorption due to the experimental uptake data best fitted with the pseudo-second-order model, also the intraparticle diffusion of ions did not significantly exert effects on the adsorption. The maximum adsorption uptake was 48 mg/g depending on the Langmuir model. Compared with other adsorbents, the MPKD was considered a promising adsorbent in the field of water treatment.